High Water Content Peat Soil Improved by MICP Technique with Fiber-Reinforcement - Chen, M.; Gowthaman, S.; Nakashima, K.; Komatsu, S.; Kawasaki, S. (11th International Conference on Geotechnique, Construction Materials and Environment, GEOMATE International Society, 2021)
Peat soil is referred to as problematic soil that uniquely forms under anaerobic and water-saturated conditions. It is usually characterized as organic soil of high compressibility, high water content, and low shear strength. To reduce the environmental impact, instead of using cement products to stabilize it, a relatively novel technique based on the bio-mineralization principle, microbially induced carbonate precipitation (MICP), was adopted to improve the soil matrix. Besides, this study introduced wastepaper fibers from the paper recycling process onto MICP treatment. The objectives were to investigate the effects of fiber reinforcement (0-50% addition) on the undrained shear strength (USS) improvement and contributing factors to the MICP effectiveness. Furthermore, the fiber-reinforced and MICP treated samples were subjected to dispersive crumb tests to examine their stability under a water-logged environment. The results showed a significant improvement in USS up to 360 folds observed when 50% of fibers were introduced onto MICP treatment. The dispersion tests revealed a stable state of MICP treated sample with fiber reinforcement, while the fiber reinforcement alone showed a swelling behavior.
Keywords: Peat soil; Microbially induced carbonate precipitation (MICP); Wastepaper fiber; Fall cone test; Dispersive crumb test